Variable inhibition of cell-free translation by HIV-1 transcript leader sequences. - Geballe, A P (1992)
The 5' ends of all human immunodeficiency virus type I (HIV-1) transcripts have the potential to coordinately regulate translation of HIV-1 mRNAs. Conflicting observations of the translational impact of these sequences in various systems stimulated these analyses of translation in reticulocyte lysates. We report a sensitive, rapid, quantitative, and inexpensive cell-free translation assay in which translational efficiency is monitored by enzymatic assay of the translation products. Using this assay and conventional radiolabeling assays, we demonstrate that the HIV-1 transcript leader inhibits downstream translation and that the stem-loop structure is required. Under our assay conditions, this inhibition occurs predominantly in cis and is not mediated by the 68 kD, interferon-induced, double-stranded RNA-activated kinase (p68). However, under other assay conditions the HIV-1 leader may activate p68 and inhibit translation in trans. We show that variation between individual preparations of cell-free extracts can dramatically alter the magnitude of the translational inhibition by the HIV-1 leader. Further, we provide evidence that a heat-labile factor is required for efficient translation of transcripts containing the HIV-1 leader. These observations provide a foundation for identifying factors required for translation of HIV-1 transcripts.